PENGENALAN BERETIKA KOMUNIKASI DIKALANGAN REMAJA PUTRI DI SMP SWASTA AMANAH TAHFIDZ QUR’AN DELI SERDANG - Butarbutar, Maria Haryanti; Lasmawanti, Sri; Lestari, Kartika Dwi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Forms of communication and interaction between people have now developed following technological developments. There are still many teenagers who use social media without heeding the values ​​and norms and principles of decency. This community service activity aims to provide an understanding of the ethics of communicating through social media among adolescents. Therefore, we carry out community service to conduct "Introduction to Ethical Communication Among Young Women at Amanah Private Middle School, Deli Serdang". Methods community service begins with observing the environment of the Amanah Deli Serdang Middle School. After the surveyed places the target. This activity was carried out with a series of stages that were arranged systematically. The distribution of respondents according to communication ethics before education was carried out from the number of respondents who were at Amanah Tahfiz Middle School totaled 36 students (100%). Ethics communicated well by 10 people (27.8%), sometimes communicated ethically by 22 people (61.1%) and communicated by bad ethics by 4 people (11.1%).